Asprosin: A Novel Player in Metabolic Diseases - Yuan, Mingyang; Li, Weidong; Zhu, Yan; Yu, Boyao; Wu, Jing (Frontiers in Endocrinology, 2020)
Asprosin, a novel glucogenic hormone, is encoded by two exons (exon 65 and exon 66) of the gene Fibrillin 1 (FBN1) and mainly synthesized and released by white adipose tissue during fasting. Asprosin plays a complex role in the central nervous system (CNS), peripheral tissues, and organs. It is involved in appetite, glucose metabolism, insulin resistance (IR), cell apoptosis, etc. In this review, we will summarize the newly discovered roles of asprosin in metabolic diseases including diabetes, obesity, polycystic ovarian syndrome (PCOS), and cardiovascular disease (CVD), which may contribute to future clinical diagnosis and treatment.